2019
DOI: 10.2147/ijwh.s218441
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sexual behavior and infection with cervical human papillomavirus types 16 and 18</p>

Abstract: ObjectiveThis study assessed whether sexual behavior, including engaging in early sexual intercourse and having had multiple sexual partners, can predict the risk of infection with cervical human papillomavirus (HPV) types 16 and 18.MethodsRecords were reviewed of women who underwent cervical cancer screening and were found to be infected with high-risk HPV. The genotypes of high-risk HPV were categorized as HPV 16, HPV 18, and other than 16 or 18. Early sexual intercourse was defined as first sexual intercour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
16
0
2
Order By: Relevance
“…In the indigenous population studied, only the number of sexual partners was found to show a relationship with LSIL (Table 1), which is in agreement with previous reports that indicate a close relationship of this factor with the development of cervical neoplasm (Herrero et al, 1990;Itarat et al, 2019). Other factors such, as parity and age of first sexual encounter, have been related to premalignant lesions and cervical cancer development (Lukac et al, 2018;Kashyap et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In the indigenous population studied, only the number of sexual partners was found to show a relationship with LSIL (Table 1), which is in agreement with previous reports that indicate a close relationship of this factor with the development of cervical neoplasm (Herrero et al, 1990;Itarat et al, 2019). Other factors such, as parity and age of first sexual encounter, have been related to premalignant lesions and cervical cancer development (Lukac et al, 2018;Kashyap et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Although participants reported a relatively low number of sexual partners (median, 1), those who reported having multiple sexual partners (≥2) in the last year had a 2-fold increased risk of hrHPV infection, consistent with well-established literature. 26,27 Studies have shown that both lifetime and recent sexual partners are positively associated with hrHPV detection in PWC in clinic 26 and self-collected samples. 10,11 Younger age of first sexual intercourse has also been shown to increase the risk of acquiring hrHPV infection 26 ; however, this was not seen in our sample.…”
Section: |mentioning
confidence: 99%
“…26,27 Studies have shown that both lifetime and recent sexual partners are positively associated with hrHPV detection in PWC in clinic 26 and self-collected samples. 10,11 Younger age of first sexual intercourse has also been shown to increase the risk of acquiring hrHPV infection 26 ; however, this was not seen in our sample. We also expected to find associations of hrHPV risk with younger age, current smoker, and history of abnormal Pap test finding as reported in prior studies 10,28 ; although we observed trends consistent with literature, our estimates were relatively imprecise, thus limiting interpretation.…”
Section: |mentioning
confidence: 99%
“…There is a risk for all women that HPV infections may become chronic and cause precancerous lesions, which may progress to invasive cancer ( Figure 1). HPV subtypes 16 and 18 are associated with 70% of invasive cervical cancers worldwide [6]. HPVs have circular, double-stranded DNA genomes that encode eight genes, of which E6 and E7 have transforming properties and are necessary for malignant conversion.…”
Section: Pathogenesis Of Hpv In Cervical Cancermentioning
confidence: 99%
“…It was recently shown that high-risk HPV genotypes affecting at least 10% of sex workers in order of decreasing frequency were HPV genotypes 52, 16, 35, 51, 33, 31, 18, and 45 [ 44 ]. It has been established that a higher number of lifetime sexual partners facilitates co-infection with multiple types of HPV and other STIs [ 6 ]. An estimated percent of 0.5% of women aged from 15 to 49 in Senegal was reported to be infected with HIV (total population of 15.85 million) [ 45 ].…”
Section: Cervical Cancer Screenings In Mali and Senegalmentioning
confidence: 99%